The first evangelization and the identity of Latin America - Martínez Ferrer, Luis (2009)
There are three positions on the relationship between the first evangelization of Latin America and the indigenous cultures: a) the Gospel fertilized perfectly and from the beginning in the indigenous cultures (triumphalist thesis); b) the Gospel was an instrument of European domination, an imposition that ancestral religiosity was unable to subdue (resistance thesis, reflected in some authors of Indian theology); c) Latin America is a mestizo continent whose population is predominantly Catholic, the result of a slow process of evangelization, with phenomena of syncretism that were, little by little, concentrating in marginal areas (thesis of nuanced realism).